The Missions of San Antonio, Texas. Architecture as a holistic representation of the environment (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
This paper analyzes the development of San Antonio missions’ cultural landscape to address the dialectic relationship between urban models created for the New World, European ideologies, and the role and contributions of the Indigenous population. During the 18 century, the need to improve the Christianizing of the Americas, associated with the urge to defend the territory of the Viceroyalty of New Spain, prompted Franciscan missionaries to open new settlements in Texas. Five of these are still standing in the current metropolitan area of San Antonio. The region’ s marginal location and the site’ s strategic position favored the growth of such Franciscan Missions under the protection of the Spanish Crown. The territory, in itself fertile, was re-shaped through substantial infrastructural and technological innovations. A complex system of artificial canals allowed the development of agricultural fields – the ejidos, or common lands – characterized by high and regular productivity, being able to feed the Mission population. Furthermore, rancherías (i.e., ranch lands) were established and designed for gazing. The local native population, commonly known as Coahuiltecos, rapidly converted from a nomadic, hunter-gatherer lifestyle to begin farming. The construction of fortified villages was the core of these newly founded communities. They had the specific role of controlling the territory and shaping Indigenous people’ s customs to be integrated within the novo-Hispanic society. The Mission settlements originated utilizing specific layout principles, hybridizing European models, such as the ones of medieval abbeys and architectural and military treatises. These settlements embody one of the most successful examples of Franciscan utopia.Keywords: San Antonio, missions, acequias, novo-Hispanic society, cultural landscape.